PENGELOLAAN DESA WISATA KARANGSAMBUNG KEBUMEN BERBASIS COMMUNITY BASED TOURISM - Arini Shofi Elmia; Alexander Reyaan; Endah Trihayuningtyas; Zulhelfa Zulhelfa (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis research aims to create a model for Karangsambung Tourism Village Management Based on Community Based Tourism Concept in Kebumen Regency. Community-based tourism development in Karangsambung Village still faces various problems, including differences in the way actors are involved in managing the village, many tourism development initiatives by villages and communities have failed or stopped after running for a while, and the tourism concept developed is not following local conditions. and ignoring developments in tourism market trends. Therefore, the concept of Community Based Tourism is considered suitable for the development of community-based tourism. This research uses a qualitative approach with descriptive methods. Resource persons were presented from various stakeholders/actors involved in the development of the Karangsambung tourist village. Through the survey results, it was found that 5 achievements must be met in developing community-based tourism villages, namely involving local communities, protecting the environment and natural resources, improving the quality of tourism services and products, utilizing technology and innovation, and supporting the local economy.Keywords: Tourism Village; Community-Based Tourism; Rural AreaAbstrakTujuan dibuatnya penelitian ini adalah merekomendasikan Pengelolaan Desa Wisata Karangsambung Berbasis Community Based Tourism (CBT) Di Kabupaten Kebumen. Pengembangan pariwisata berbasis Masyarakat di Desa Karangsambung masih menemui berbagai permasalahan diantaranya masih adanya perbedaan cara pandana aktor yang terlibat dalam pengelolaan desa, banyak inisiasi pengembangan wisata oleh desa dan komunitas yang gagal atau berhenti setelah berjalan beberapa saat, konsep wisata yang dikembangkan tidak sesuai dengan kondisi lokal serta mengabaikan perkembangan trend pasar pariwisata. Karenanya konsep Comunity Based Tourism dinilai cocok dikembangkan oleh wisata berbasis komunitas. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Narasumber dihadirkan dari berbagai pemangku kepentingan/aktor yang terlibat dalam pengembangan desa wisata Karangsambung. Melalui hasil survei didapatkan 5 capaian yang harus dipenuhi dalam pengembangan desa wisata berbasis masyarakat yaitu pelibatan masyarakat lokal, menjaga lingkungan dan SDA, meningkatkan kualitas layanan dan produk wisata, memanfaatkan teknologi dan inovasi, serta mendukung ekonomi lokal.Kata Kunci: Desa Wisata; Community-Based Tourism; Pedesaan